2016
DOI: 10.1055/s-0035-1570083
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function Testing in Patients on Antiplatelet Medications

Abstract: Guidelines provide a Class IA recommendation for the use of dual antiplatelet therapy in patients undergoing percutaneous coronary intervention (PCI). However, there is interindividual variability in the pharmacodynamic response to antiplatelet medications. Some patients present with a status of high on-treatment platelet reactivity (HPR) during platelet function testing after standard doses of antiplatelet drugs, reflecting a failure to achieve adequate platelet inhibition. As an example, patients with HPR on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…The metabolism of clopidogrel into its active metabolites is affected by individual polymorphisms of CYP enzymes (Jarrar et al, 2016). Patients with high on-treatment platelet reactivity upon clopidogrel were at increased risk for thrombotic events, particularly for stent thrombosis and myocardial infarction, but cardiovascular mortality was also elevated in patients undergoing percutaneous coronary intervention (Gross et al, 2016). It was reported that aspirin use after discharge for HF hospitalization was associated with reduced risk of death, all-cause readmission, and HF readmission (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of clopidogrel into its active metabolites is affected by individual polymorphisms of CYP enzymes (Jarrar et al, 2016). Patients with high on-treatment platelet reactivity upon clopidogrel were at increased risk for thrombotic events, particularly for stent thrombosis and myocardial infarction, but cardiovascular mortality was also elevated in patients undergoing percutaneous coronary intervention (Gross et al, 2016). It was reported that aspirin use after discharge for HF hospitalization was associated with reduced risk of death, all-cause readmission, and HF readmission (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are various approaches for platelet function assessment, and most of them focus on the measurements carried out after platelet activation caused by agonist administration (Koltai et al, 2017;Ostrowska et al, 2019). Despite the wide range of available tests, some are discussed below, new, more sensitive and specific biomarkers are needed, especially for the monitoring of antiplatelet therapy (Gross et al, 2016). It has been revealed in some research that sP-selectin or CD40L might serve as such biomarkers, but their detectability time in general circulation is short (Yun et al, 2016).…”
Section: Determination Of Platelet Function On Antiplatelet Therapymentioning
confidence: 99%
“…Current cardiology guidelines define LPR, optimal PR (OPR), and HPR categories as <95, 95-208, and >208 PRU for VerifyNow testing. 32 Similar to aspirin treatment, 33 the presence of risk factors seems a significant contributor to the clinical relevance of HPR and outcome. 34 A meta-analysis of 6,000 individual on-clopidogrel patient data 35 showed that HPR was prognostic for MACE in a dose-dependent fashion.…”
Section: Phenotyping and Clinical Outcomementioning
confidence: 99%